Precise control of intramolecular charge-transport: The interplay of distance and conformational effects - Schubert, Christina; Wielopolski, Mateusz; Mewes, Lars-Hendrik; De Miguel Rojas, Gustavo; Van Der Pol, Cornelia; Moss, Kathryn C.; Bryce, Martin; Moser, Jacques E.; Guldi, Dirk Michael; Clark, Timothy (Chemistry - A European Journal, 2013)
A new series of donor-bridge-acceptor (D-B-A) compounds consisting of π-conjugated oligofluorene (oFL) bridges between a ferrocene (Fc) electron-donor and a fullerene (C) electron-acceptor have been synthesized. In addition to varying the length of the bridge (i.e., mono- and bi-fluorene derivatives), four different ways of linking ferrocene to the bridge have been examined. The Fc moiety is linked to oFL: 1) directly without any spacer, 2) by an ethynyl linkage, 3) by a vinylene linkage, and 4) by a p-phenylene unit. The electronic interactions between the electroactive species have been characterized by cyclic voltammetry, absorption, fluorescence, and transient absorption spectroscopy in combination with quantum chemical calculations. The calculations reveal exceptionally close energy-matching between the Fc and the oFL units, which results in strong electronic-coupling. Hence, intramolecular charge-transfer may easily occur upon exciting either the oFLs or Fcs. Photoexcitation of Fc-oFL-C conjugates results in transient radical-ion-pair states. The mode of linkage of the Fc and FL bridge has a profound effect on the photophysical properties. Whereas intramolecular charge-separation is found to occur rather independently of the distance, the linker between Fc and oFL acts (at least in oFL) as a bottleneck and significantly impacts the intramolecular charge-separation rates, resulting in beta values between β 0.08 and 0.19 Å. In contrast, charge recombination depends strongly on the electron-donor-acceptor distance, but not at all on the linker. A value of β (0.35±0.01 Å) was found for all the systems studied. Oligofluorenes prove, therefore, to be excellent bridges for probing how small structural variations affect charge transport in D-B-A systems. Finely tuned transfer: Chemical modification of the oligo-fluorene linkers between Fc and C units enables fine-tuning of photoinduced charge-transfer processes in new donor-bridge-acceptor conjugates (see illustration). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.